2018
DOI: 10.1080/10717544.2018.1461279
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of kartogenin-conjugated polyurethane nanoparticles attenuates the progression of osteoarthritis

Abstract: Osteoarthritis (OA) is the most common form of joint disease and a leading cause of physical disability, there is an urgent need to attenuate the progression of OA. Intra-articular (IA) injection is an effective treatment for joints diseases, however, the therapeutic effects mostly depend on the efficacy of drug duration in joints. Drug delivery system can provide drug-controlled release and reduce the number of IA injection. In this study, amphiphilic polyurethanes with pendant amino group were synthesized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…In addition, when cultured in KGN thermogel, OA chondrocytes produced higher amount of GAG and COL-2 than those in thermogel without addition of KGN. These data are consistent with others which showed that KGN promoted cartilage regeneration and induced chondrogenic differentiation of mesenchymal stem cells (Kang et al, 2014, 2016; Wang et al, 2016b; Fan et al, 2018; Han et al, 2019). In addition, the level of MMP-13 produced by OA chondrocytes in KGN thermogel was much less compared to that in thermogel.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, when cultured in KGN thermogel, OA chondrocytes produced higher amount of GAG and COL-2 than those in thermogel without addition of KGN. These data are consistent with others which showed that KGN promoted cartilage regeneration and induced chondrogenic differentiation of mesenchymal stem cells (Kang et al, 2014, 2016; Wang et al, 2016b; Fan et al, 2018; Han et al, 2019). In addition, the level of MMP-13 produced by OA chondrocytes in KGN thermogel was much less compared to that in thermogel.…”
Section: Discussionsupporting
confidence: 92%
“…Recently a small molecule, kartogenin (KGN), has been reported to promote collagen synthesis (Johnson, 2012). Intra-articular injection of KGN has been reported to enhance cartilage regeneration (Kang et al, 2014; Mohan et al, 2016; Fan et al, 2018). However, KGN cannot provide long-term therapeutic effects due to fast clearance and short retention of KGN in joints, posing a disadvantage in its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most attractive polymer candidates, poly(lactic-co-glycolic acid) (PLGA)—a typical compound used in fabrication of biodegradable microspheres or nanoparticles, which has been approved for use by the Food and Drug Administration—is widely used as a vehicle for delivery of pharmaceutically relevant payloads ( Danhier et al, 2012 ; Fernando et al, 2018 ). Furthermore, the amino groups of PLGA can bind covalently to the carboxyl groups of KGN, thus enhancing the permeability and retention of KGN and promoting its therapeutic effects ( Kang et al, 2014 ; Fan et al, 2018 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kartogenin (KGN), a heterocyclic‐structured small‐molecule compound, can promote the chondrogenic differentiation of MSCs and protect chondrocytes from ossification (12). The applications of KGN in tissue engineering and regenerative medicine have been widely expanded since its discovery, including musculoskeletal, meniscal, and articular cartilaginous regeneration strategies (1315). However, the efficiency of chondrogenesis induced by KGN alone has been far from satisfactory, impeding its further clinical application (16, 17).…”
mentioning
confidence: 99%